In Vivo Assessment of Ferroptosis and Ferroptotic Stress in Mice. Issue 4 (5th April 2022) - Ide, Kana; Souma, Tomokazu
Abstract: Ferroptosis is iron‐dependent, lipid peroxidation–driven, regulated cell death that is triggered when cellular glutathione peroxidase 4 (GPX4)‐mediated cellular defense is insufficient to prevent pathologic accumulation of toxic lipid peroxides. Ferroptosis is implicated in various human pathologies, including neurodegeneration, chemotherapy‐resistant cancers, ischemia‐reperfusion injury, and acute and chronic kidney diseases. Despite the fact that the ferroptotic process has been rigorously interrogated in multiple preclinical models, the lack of specific and readily available biomarkers to detect ferroptosis in vivo in mouse models makes it challenging to delineate its contribution to key pathologic events in vivo . Critical steps to practically evaluate ferroptosis include, but are not limited to, detecting increased cell death and pathologic accumulation of toxic lipid peroxides and testing augmentation of observed pathologic events by genetic inhibition of the glutathione‐GPX4 axis or mitigation of the pathologic process by ferroptosis inhibitors. Here, we describe methods to evaluate these key features of the ferroptotic process in mice in vivo . Specifically, we describe methods to detect toxic lipid peroxides (4‐hydroxynonenal) and cell death (based on terminal deoxynucleotidyl transferase dUTP nick end labeling staining) as well as a protocol to pharmacologically inhibit ferroptotic stress using liproxstatin‐1. These protocols provide tools for understanding the ferroptotic process in mouse genetic or disease models. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : How to use liproxstatin‐1 Basic Protocol 2 : How to evaluate ferroptosis in mouse kidneys